265 Group and Saves for Laparoscopic Cholecystectomies: An Unnecessary Expense?. (19th August 2022) - Cole, K; Jamnadass, E; Ward, J; Hou, D
Abstract: Aim: The aim of this study was to analyse the necessity of routine group and saves (G+S) in patients undergoing laparoscopic cholecystectomies and to establish whether it would be safe to cease this practice. In doing so, we aim to reduce financial burden and workload, whilst maintaining safe clinical outcomes. Method: This was a retrospective study into all consecutive patients that underwent an elective or emergency laparoscopic cholecystectomy in Royal Hampshire County Hospital (RHCH) from May 2019 - May 2021. IT systems and clinical notes were analysed to identify the quantity of pre-operative G+S samples sent, and the proportion of patients that required a postoperative blood transfusion. Results: Over 24 months, 427 laparoscopic cholecystectomies were performed in RHCH, 70% of which were elective. In total, 682 G+S samples were processed (1.6/patient), resulting in a cost of £16504. Two patients received a postoperative blood transfusion (0.5%). One of these patients presented with an UGI bleed, whilst the other presented with a haemolytic crisis. They were therefore predictable, pre-operative conditions, for which a post-operative transfusion had been planned prior to surgery. Conclusion: In conclusion, this study suggests that performing routine G+S for all laparoscopic cholecystectomy patients has created an unnecessary workload and financial burden on this small DGH. Furthermore, during this 24 month, this practice had no clinical advantage. We therefore advise that sending pre-operative G+S samples should be a clinical decision made on a case-by-case basis, rather than a default for all patients.